Medico-social characteristics of patients at the psycho-somatic department - L. V. Kochorova; V. S. Skripov; G. A. Ivanova; E. B. Zakharova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2016)
Over the recent years, there has been an increase in the number of patients with psychosomatic disorders, as well an increase in the number of «masked depressions». High social significance of psychosomatic diseases is predetermined by the fact that it is extremely common among people of working age. The aim of the study was to analyze the medical and social composition of the patients at the psychosomatic department, as well as to show the efficiency of treatment in such department. The analysis of data obtained during the survey department of psychosomatic patients for anxiety and depressive disorders is presented. The survey was conducted by using the Hospital Anxiety and Depression Scale (HADS). The medical documentation of the department was also analyzed. The study found that the social composition of patients was heterogenous. Most of the patients (54.3 %) were in hospital with a diagnosis of organic anxiety disorder. It was revealed that the largest share among the somatic pathology accounted to such pathology as hypertension of the III degree in conjunction with coronary artery disease (20.7 %) and hypertension of the II stage (19.6 %). The efficacy of treatment in this department was proven. By the 20th day of hospitalization, 30 % of patients did not experience anxiety and/or depression. Combined symptoms of anxiety and depression were observed only in 14 % of patients by the 20th day of treatment.